The role of economic and policy variables in energy-efficient retrofitting assessment. A stochastic Life Cycle Costing methodology. (June 2019) - Baldoni, Edoardo; Coderoni, Silvia; D'Orazio, Marco; Di Giuseppe, Elisa; Esposti, Roberto
Abstract: Energy saving is a major policy objective worldwide and in the EU in particular. Evaluating the convenience of energy-efficient investments, however, is complex. This paper aims to apply stochastic Life Cycle Costing to assess the economic value of energy-efficient building retrofitting investments. The proposed approach investigates how macroeconomic variables affect such an evaluation by explicitly taking into account their interdependent stochastic nature. Consequently, the economic evaluation of an investment is itself stochastic thus expressing both its expected value and its inherent uncertainty and risk. On this basis, an illustrative case-study is presented, where alternative designs of the energy-saving intervention are compared and a sensitivity analysis performed to identify the determinants of the LCC outcome and of its variability. In terms of policy implications, a tool providing a sounder evaluation of the convenience of such investments can suggest when and to what extent incentives may be appropriate to facilitate these investments and what possible financial instruments could be put forward in order to reduce the associated risk. Highlights: Energy saving in buildings is a main policy objective of EU Energy Union strategy. A stochastic method to include uncertainty in buildings LCC is presented. It is based on VAR modelling of interdependent macroeconomic variables. It includes a sensitivity analysis to identify the determinants of the LCC outcome. Results confirm the potential of the method for a sounder evaluation of investments.